Analisis Dinamik Model Predator-prey dengan Perilaku Anti Predator serta Efek Allee pada Prey - Hady Rasikhun; Putra, M. Adib Jauhari Dwi; Robbi, Rizka Rizqi (Eigen Mathematics Journal, 2023)
We explore a predator-prey model that incorporates both anti-predator behavior by the prey and the Allee effect, where population growth declines at low densities. Four equilibrium points emerge: extinction for both species (E0), two predator extinction points (E1 and E2), and one coexistence point for both populations (E3). While the stability of E0, E2, and E3 depends on the given parameters, E1 is always unstable. We then verified this analysis through numerical simulations using Runge-Kutta method in Python.